Methodology in the use of the Old Testament in the new: context and criteria - Allen, David M.; Smith, Steve (Library of New Testament studies, 2019)
"This volume brings together scholars of both the Old and New Testaments, to discuss three areas of methodological interest in respect of the use of the Old Testament in the New (OT/NT). It begins with an interdisciplinary conversation into insights that OT/NT scholars might glean from other related disciplines and approaches. The subsequent essays consider the notion of an Old Testament text’s ‘context’, and how contemporaneous authors such as Philo or the Qumran community conceived of, and attended to, the concept. The contributors then turn their focus to the criteria that can/should be used for determining Old Testament allusions or echoes, and the legitimacy for so doing, particularly responding to the work of Richard Hays. The volume closes with a fresh proposal for OT/NT methodology, along with a concluding reflection on the collected essays."